Active fault tolerant control applied to REPOINT, a novel railway track switch. Issue 24 (2018) - Kaijuka, Precious; Dixon, Roger; Ward, Christopher
Abstract: Railway networks are fitted with switches and crossings that enable trains to move from one track to another however they present a single point of failure. Existing track switches actuation is performed in the open loop presenting a research gap where closed-loop fault tolerant control can be applied to track switch actuation in order to improve railway network performance. A new railway track switch, REPOINT has been developed at Loughborough University with a new electromechanical design that incorporates actuator redundancy to improve the reliability of track switch operation. This paper looks at the development and validation of a sensor fault detection, identfication and accomodation scheme applied to a detailed non-linear model representing the laboratory scale demonstrator of the REPOINT concept. A residual-based fault diagnosis scheme is developed from the comparison of estimates generated by a bank of observers and output measurements. In the presence of sensor faults, a reconstructed signal from the fault detection algorithm is used to replace the measured signal for feedback control and thus safe switching position control is achieved. The results demonstrate that using a reliable fault tolerant control configuration could increase the availability and reliability of the REPOINT track switch.